2017
DOI: 10.1080/19440049.2017.1371854
|View full text |Cite
|
Sign up to set email alerts
|

Pediococcus acidolacticiandPediococcus pentosaceusisolated from a rainbow trout ecosystem have probiotic and ABF1 adsorbing/degrading abilitiesin vitro

Abstract: Probiotics are being used in biological control of bacterial pathogens, as an alternative to antibiotics, to improve health and production parameters in fish farming. Fish farming production is severely affected by aflatoxins (AFs), which are a significant problem in aquaculture systems. Aflatoxins exert substantial impact on production, causing disease with high mortality and a gradual decline of reared fish stock quality. Some aspects of aflatoxicosis in fish, particularly its effects on the gastrointestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 56 publications
0
12
0
1
Order By: Relevance
“…These results are in line with previous studies that also showed that the inclusion of terrestrial plant proteins in rainbow trout diet induces a significant increase of several LAB among other microorganisms [ 21 , 39 , 44 , 45 ]. Interestingly, several strains belonging to the genus Pediococcus displayed probiotic properties in vitro [ 46 ] and in vivo in rainbow trout [ 47 ]. In other fish species, feeds containing plant derivate indigestible fiber and fermentable polysaccharides were associated with an increase of LAB that can utilize such substrates for their metabolism and growth [ 48 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with previous studies that also showed that the inclusion of terrestrial plant proteins in rainbow trout diet induces a significant increase of several LAB among other microorganisms [ 21 , 39 , 44 , 45 ]. Interestingly, several strains belonging to the genus Pediococcus displayed probiotic properties in vitro [ 46 ] and in vivo in rainbow trout [ 47 ]. In other fish species, feeds containing plant derivate indigestible fiber and fermentable polysaccharides were associated with an increase of LAB that can utilize such substrates for their metabolism and growth [ 48 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Certain Pediococcus spp. have mycotoxin adsorbing and degrading properties ( Martinez et al, 2017 ). Reducing aflatoxin bioavailability was reported in rats ( Hernandez-Mendoza et al, 2011 ; Nikbakht Nasrabadi et al, 2013 ) and in mice ( Jebali et al, 2015 ), but yet no clinical data are available on the use of LAB as detoxifying probiotics in humans.…”
Section: Regardless Of Their Origin Lab Can Exhibit Multifaceted Funmentioning
confidence: 99%
“…, ) and probiotic Pediococcus acidolactici and P. pentosaceus (Martínez et al . ). The use of these micro‐organisms at a commercial level requires a design of the culture medium, one of the most important tasks within the biological technology, evaluating the use of economic substrates for the biomass production at a large scale, allowing also the conservation of the biological properties previously demonstrated in the laboratory.…”
Section: Introductionmentioning
confidence: 97%